Meningkatkan Prestasi Akademik dan Keterampilan Kerja Sama Peserta Didik Menggunakan Model Problem-Based Learning (PBL) pada Materi Manusia Berkembang Berkat Peran Sesama di Kelas VII SMP Negeri 4 Kayan Hilir - Maria Junai; Timotius Tote Jelahu; Modestus Haryono; Nikodemus Martin Kodinar (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the academic achievement and teamwork skills of 7th-grade students at SMP Negeri 4 Kayan Hilir by using the Problem-Based Learning (PBL) model on the topic of "Human Development Through the Role of Others." The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study were 20 7th-grade students. Data collection instruments included academic achievement tests and teamwork skills observation sheets. The results of the study showed an increase in academic achievement, from an average score of 64 in the pre-cycle to 81 in cycle II. Additionally, the students' teamwork skills improved from the "sufficient" category to "good" in cycle II. Thus, the PBL model was effective in improving both the academic achievement and teamwork skills of the students.